1981
DOI: 10.1016/0039-6028(81)90496-9
|View full text |Cite
|
Sign up to set email alerts
|

The decomposition of ammonia on the flat (111) and stepped (557) platinum crystal surfaces

Abstract: Ammonia adsorptions desorption and decomposition to H 2 and N 2 has been studied on the flat (lll) and stepped (557)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Pure ammonia does not decompose noteably on Pt surfaces below 600 K, whereas with oxygen the rate of decomposition is considerable [19,45]. On the oxygen covered stepped Pt surfaces studied here a high reactive sticking coefficient of ammonia reaching 0.2 also supports this idea [18].…”
Section: Discussionsupporting
confidence: 63%
“…Pure ammonia does not decompose noteably on Pt surfaces below 600 K, whereas with oxygen the rate of decomposition is considerable [19,45]. On the oxygen covered stepped Pt surfaces studied here a high reactive sticking coefficient of ammonia reaching 0.2 also supports this idea [18].…”
Section: Discussionsupporting
confidence: 63%
“…Reactions proposed for the activation of ammonia molecules on Pt surfaces are decomposition [46,54,55], reaction with adsorbed oxygen atoms [56,57], and reaction with adsorbed hydroxyl groups, where OH ads is generated by NH x + O interactions [19,[57][58][59][60]. DFT studies [61] confirmed that stepwise abstraction of hydrogen atoms from NH 3 by reaction with O and OH are fast compared to decomposition of NH x , and that the reaction path of ammonia decomposition can therefore be neglected.…”
Section: Suggested Reaction Mechanismmentioning
confidence: 65%
“…investigated [126][127][128][129][130][131][132][133][134][135]. These studies have been undertaken primarily to acquire insights into the industrially important ammonia synthesis process.…”
Section: Molecular Beam Epitaxymentioning
confidence: 99%